Pharmacological Characterization of 5-Substituted 1-[(2,3-dihydro-1-benzofuran-2-yl)methyl]piperazines: Novel Antagonists for the Histamine H3 and H4 Receptors with Anti-inflammatory Potential - Corrêa, Michelle F.; Barbosa, Álefe J. R.; Teixeira, Larissa B.; Duarte, Diego A.; Simões, Sarah C.; Parreiras-e-Silva, Lucas T.; Balbino, Aleksandro M.; Landgraf, Richardt G.; Bouvier, Michel; Costa-Neto, Claudio M.; Fernandes, João P. S. (Frontiers in Pharmacology, 2017)
The histamine receptors (HRs) are traditional GPCRs of extensive therapeutic interest. Recently, H3R and H4R subtypes have been targeted in drug discovery projects for inflammation, asthma, pain, cancer, Parkinson’s and Alzheimer’s diseases, which includes searches for dual acting H3R/H4R ligands. In the present work, nine 1-[(2,3-dihydro-1-benzofuran-2-yl)methyl]piperazine (LINS01 series) molecules were synthesized and evaluated as H3R and H4R ligands. Our data show that the N-allyl-substituted compound LINS01004 bears the highest affinity for H3R (pKi 6.40), while the chlorinated compound LINS01007 has moderate affinity for H4R (pKi 6.06). In addition, BRET assays to assess the functional activity of Gi1 coupling indicate that all compounds have no intrinsic activity and act as antagonists of these receptors. Drug-likeness assessment indicated these molecules are promising leads for further improvements. In vivo evaluation of compounds LINS01005 and LINS01007 in a mouse model of asthma showed a better anti-inflammatory activity of LINS01007 (3 g/kg) than the previously tested compound LINS01005. This is the first report with functional data of these compounds in HRs, and our results also show the potential of their applications as anti-inflammatory.